Survival analysis of renal patients underwent transplantation in Kyrgyz Republic and various countries by 10 years follow-up - Zhanybek J. Gaibyldaev; Zhamalbek I. Ashimov; Damirbek A. Abibillaev; Fuat Kocyigit (Heart Vessels and Transplantation, 2019)
In our study we conducted survival analysis of 204 patients visited Scientific-Research Institute of Heart Surgery and Organs transplantation and who underwent renal transplantation in Kyrgyzstan and other Eurasian countries between 2005 and 2016 years (age range: 9-71 years, mean: 38.21 (12.74) years, median: 34.0 (0.89) years; gender: 142 male (69.6%)).